Educational technology on tuberculosis: construction shared with Primary Health Care nurses - Aloma Sena Soares; Laura Maria Vidal Nogueira; Erlon Gabriel Rego de Andrade; Élida Fernanda Rêgo de Andrade; Ivaneide Leal Ataíde Rodrigues (Revista Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to develop, in a participatory way, an educational technology to assist nurses in the management of tuberculosis cases in Primary Health Care. Methods: methodological research with a qualitative approach. Data were collected between June and October 2022, in 25 Basic Health Units, with 41 nurses interviewed individually. Thematic content analysis was carried out to guide technology elaboration. Results: three empirical categories were organized, demonstrating the facilities and difficulties in tuberculosis management, the conceptions about educational technology as a facilitator of the teaching-learning process in Primary Health Care and participatory development of technology. Nurses were in favor of constructing an instructional guide technology, and made suggestions to encourage its creation and use in daily service routine. Final considerations: the participatory process made it possible to create technology to assist nurses in the teaching-learning process in Primary Health Care about caring for people with tuberculosis.